Neutrophil-to-albumin ratio predicts long-term prognosis in coronary heart disease: a prospective cohort study of 2,990 patients - Wu, Hao; Feng, Kaiyue; Hua, Yiming; Lin, Zehao; Ding, Ning; Xie, Yifei; Xu, Yu; Wu, Yue; Cheng, Danyu (Frontiers in Nutrition, 2025)
BackgroundCardiovascular diseases (CVDs), particularly coronary heart disease (CHD), impose a global health burden with unpredictable major adverse cardiovascular events (MACE) despite optimal treatment. Systemic inflammation and malnutrition are key pathogenic drivers, yet integrated biomarkers capturing this duality are lacking. The Neutrophil-to-Albumin Ratio (NPAR) emerges as a cost-effective indicator reflecting both pathways, but its prognostic value for post-discharge MACE in hospitalized CHD patients remains unestablished. Our study aimed at investigating the prognostic value of NPAR for MACE in CHD patients.MethodsThis prospective cohort study enrolled CHD patients (2013–2020) from the First Affiliated Hospital of Xi’an Jiaotong University. NPAR was calculated from admission blood samples. Participants were stratified into NPAR tertiles (T1: 5.21–16.00; T2: 16.01–18.50; T3: 18.51–42.38). Multivariable Cox models (adjusting for demographics, comorbidities, and laboratory parameters) assessed NPAR-MACE associations. Restricted cubic splines (RCS) and subgroup analyses explored nonlinearity and effect modifiers.ResultsA total of 2,990 patients with CHD were eligible for analysis. With a median follow-up of 70 months, Kaplan–Meier survival curves demonstrated that participants in the highest NPAR tertile (T3) exhibited significantly lower cumulative survival rates free from MACE compared to those in the lowest tertile (T1). The highest NPAR tertile (T3) exhibited a 72% increased MACE risk (adjusted hazard ratio (HR) = 1.72, 95% confidence interval (CI): 1.36–2.20) versus T1. A J-shaped relationship emerged, with risk escalating above NPAR = 17 (P nonlinear = 0.01). Sex-specific heterogeneity was observed: males in T3 had markedly elevated risk (HR = 2.03, 95% CI: 1.50–2.75; P interaction = 0.03).ConclusionElevated admission NPAR independently predicts long-term MACE in CHD patients, particularly among males. This supports NPAR’s utility for post-discharge risk stratification.